Mott Transition of the Half-filled Hubbard Model in a Two-dimensional Frustrated Lattice - Tuan, Hoang Anh; Anh, Le Duc (Communications in Physics, 2013)
Using coherent potential approximation we study zero-temperature Mott transition of the half-filled Hubbard model in a two-dimensional square lattice with geometrical frustration. It turns out that the geometrical frustration reduces the gap between the Hubbard bands. As a result the metallic phase is stabilized up to a fairly large value of the on-site Coulomb interaction. We found that the critical value U_C for the Mott transition is enhanced by the geometrical frustration. Our results are in good agreement with the ones obtained by the single-site dynamical mean-field theory.